Molecular alterations of the Fyn-complex occur as late events of human T cell activation - Marie-Cardine, Anne; Kirchgessner, Henning; Schraven, Burkhart (European journal of immunology, 1999)
Two-dimensional gel electrophoresis of anti-p59fyn immunoprecipitates obtained from non-transformed resting human T lymphocytes resulted in the identification of an oligomeric protein complex which is constitutively formed between Fyn and several additional phosphoproteins (pp43, pp72, pp85, the protein tyrosine kinase Pyk2, as well as the two recently cloned adaptor proteins, SKAP55 and SLAP-130). With the exception of pp85, these proteins seem to preferentially interact with Fyn since they are not detectable in Lck immunoprecipitates prepared under the same experimental conditions. Among the individual members of the Fyn-complex pp85, SKAP55 and pp43 are constitutively phosphorylated on tyrosine residue(s) in vivo and likely interact with Fyn via its src homology 2 (SH2)-domain. In contrast to non-transformed T lymphocytes, continuously proliferating transformed human T cell lines express an altered Fyn-complex. Thus, despite normal expression and tyrosine phosphorylation, SKAP55 does not associate with Fyn in Jurkat cells and in other human T cell lines. Instead two novel proteins interact with Fyn among which one has previously been identified as α-tubulin. Importantly, almost identical alterations of the Fyn-complex as observed in Jurkat cells are induced in non-transformed T lymphocytes following mitogenic stimulation. These data suggest that Fyn and its associated proteins could be involved in the control of human T cell proliferation. Moreover, the analogous constitutive alterations in transformed T cell lines could indicate that deregulation of the Fyn-complex might be functionally associated with the malignant phenotype of these cells.
First published: 28 March 2006
Gesehen am 08.03.2021